2007
DOI: 10.1016/j.cemconres.2007.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Pore structure and mechanical properties of cement–lime mortars

Abstract: Studies focusing on materials used in Cultural Heritage conservation projects are becoming increasingly important. In this paper, pore structure and mechanical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(94 citation statements)
references
References 23 publications
10
79
1
4
Order By: Relevance
“…The smaller total porosity and reduced threshold pore size and consequently lower pore connectivity are found in HCPs due to the inclusion of PCE, which results from the dispersing effect of PCE in FCPs and the heightened cement hydration degree. The results are consistent with previous reports of others (Arandigoyen and Alvarez 2007;Khatib and Mangat 1999;Sakai et al 2006). The pore size distribution and the pore volume of HCPs cured for 28 days are slightly affected by the addition of PCE, while with the growth in P/C, obvious decline in the entrapped mercury volume is presented due to the better dispersion of cement grains in FCPs.…”
Section: Pore Structure Of Hcps With W/c Of 029supporting
confidence: 82%
“…The smaller total porosity and reduced threshold pore size and consequently lower pore connectivity are found in HCPs due to the inclusion of PCE, which results from the dispersing effect of PCE in FCPs and the heightened cement hydration degree. The results are consistent with previous reports of others (Arandigoyen and Alvarez 2007;Khatib and Mangat 1999;Sakai et al 2006). The pore size distribution and the pore volume of HCPs cured for 28 days are slightly affected by the addition of PCE, while with the growth in P/C, obvious decline in the entrapped mercury volume is presented due to the better dispersion of cement grains in FCPs.…”
Section: Pore Structure Of Hcps With W/c Of 029supporting
confidence: 82%
“…Lange [10] explored several image analysis techniques that provide insight into the nature of pore structure as observed in backscattered electron images of polished sections. In Arandigoyen et al [11], microstructure of blended mortars is studied taking into account porosity, pore size distribution and surface fractal dimension, meanwhile Diamond et al [12] have shown that pore systems of concrete may present fractal characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo se han documentado algunos elementos que determinan el estado de conservación de los morteros, en tanto que dicho estado de conservación queda condicionado por la calidad de las manufacturas, como la presencia de poro o de nódulos, que condiciona sus características físicas y mecánicas (Arandigoyen, y Álvarez, 2007), o el tamaño y dosificaciones de los áridos, que pueden determinar la respuesta de los morteros ante las tensiones (Hormes et al, 2016: 191).…”
Section: Resultsunclassified